2011
DOI: 10.1016/j.patcog.2010.08.028
|View full text |Cite
|
Sign up to set email alerts
|

On Euclidean norm approximations

Abstract: Euclidean norm calculations arise frequently in scientific and engineering applications. Several approximations for this norm with differing complexity and accuracy have been proposed in the literature. Earlier approaches [1,2,3] were based on minimizing the maximum error. Recently, Seol and Cheun [4] proposed an approximation based on minimizing the average error. In this paper, we first examine these approximations in detail, show that they fit into a single mathematical formulation, and compare their avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Note the striking similarity between (5) and (6). Interestingly, a similar but less rigorous approach had been published earlier by Ohashi [9].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Note the striking similarity between (5) and (6). Interestingly, a similar but less rigorous approach had been published earlier by Ohashi [9].…”
Section: Introductionmentioning
confidence: 58%
“…In a recent study [6], we examined various Euclidean norm approximations in detail and compared their average and maximum errors using numerical simulations. Here we show that two of those approximations, namely Barni et al's norm [1,7] and Seol and Cheun's norm [8], are viable alternatives to D M .…”
Section: Introductionmentioning
confidence: 99%
“…Note also that these two norms are much more naturally linearizable norms than the Euclidean norm. The most recent works ( [7], [19]) on the subject showed that in the Euclidean plane, the best maximum relative error of an optimized combination of the L 1 and L ∞ norms with respect to the L 2 norm is approximately equal to 5.6%. In the same paper the best combination of an overestimating norm, the euclidean Chamfering weighted distance in 2-D, and an underestimated norm, the Inverse square root weighted t-cost distance in 2-D provide the best empirical MRE of 1.29%.…”
Section: Linearization Of Euclidean Norm Dependent Constraints In Rmentioning
confidence: 99%
“…Assuming d 2 ,r) is considered (in the calibration procedure we will show how to calculate out these average features). Afterwards, the Euclidean norm of local feature vectors is calculated [23] by the following formula, respectively: Obtained. It should be underlined that, differently from [24], norm-1 has been used.…”
Section: Figure 2 Perspective View Of (A) Even and (B) Odd Parts Of mentioning
confidence: 99%